L’assureur-vie face aux exigences d’un marché en évolution - Moffet, Denis (Assurances, 1990)
ln his article, our collaborator first describes the savings market in Canada and shows how life insurance competes with other types of savings. He then describes the life insurer's need to adapt and, more particularly, the difficulty in reconciling the sales function with the consulting function. Can the same person excel in both sales and consulting? According to the author, this is possible if the individual has the proper university background.